GC-MS ANALYSIS OF VOLATILE COMPONENTS IN PETROLEUM ETHER EXTRACTS OF COLDENIA PROCUMBENS LINN. - PROF B.KESAVA RAO,; G.USHA RANI, (International Journal of Pharma and Bio Sciences, 2016)
Coldenia procumbens Linn. is a procumbent, deep rooted, hairy herb and very rare valuable medicinal plant species belongs to Boraginaceae family. The present work deals with the GC-MS analysis of petroleum ether extract of Coldenia procumbens Linn. The results had shown many compounds with different peak areas showing highest peak area percentage for 9,12-Octadecadienoic acid and least peak area percentage for Stigmast-4-en-3-one. The results of this study will give information about the occurrence of different types of chemical compounds from Coldenia procumbens Linn. along with their significant pharmacological active properties.